Implementasi Pembelajaran Antre sebagai Upaya Penguatan Regulasi Emosi Anak Usia Dini - Khoirun Nisa; Nurul Azizah; Ariq Nurjannah Irbah; Desika Putri Mardiani (LP3M STAI MA'ARIF MAGETAN, 2025)
This study aims to describe the implementation of queue-based learning as an effort to strengthenemotional regulation in early childhood. The study employed a qualitative approach with a descriptivedesign. The subjects were children aged 4–6 years in an early childhood education setting, with teachersserving as supporting informants. Data were collected through observation, interviews, anddocumentation. Data analysis used an interactive model consisting of data reduction, data display, andconclusion drawing, with data validity ensured through source and technique triangulation. The resultsshowed that initially, children demonstrated limited emotional regulation skills, characterized byimpatience, emotional outbursts, and difficulty waiting for their turn. After consistent implementation ofqueuing activities, there was a noticeable improvement in children’s emotional regulation, includingincreased ability to wait calmly, follow rules, and reduce impulsive behavior. Queuing activities alsofacilitated the internalization of social values such as discipline, patience, and respect for others. Thesefindings indicate that queue-based learning can serve as an effective strategy to develop emotionalregulation in early childhood through direct social experiences. This study implies that simple dailyactivities can be optimized as meaningful tools for social-emotional learning in early childhood education.